Originally Posted by

**jjstuart** Hi,

Im trying to teach myself the substitution rule for integrals and am having a problem with the formula. I'm not grasping something here and hope someone can help me out.

Here is the integral I'm working with.

4x^3 * sqrt(x^4 + 7) dx

The formula says f(g(x)g'(x)dx = Integral f(u) du

To me that says to take f(u) * du, but when they work the problem out it seems that they just drop the du.

If we start out with the integral

4x^3 * sqrt(x^4 + 7) dx

g(x) = u

u = x^4 + 7

du = 4x^3 dx